Cover Feature: Tunable Ligand Effects on Ruthenium Catalyst Activity for Selectively Preparing Imines or Amides by Dehydrogenative Coupling Reactions of Alcohols and Amines (Chem. Eur. J. 52/2017). Issue 52 (1st August 2017) - Higuchi, Takafumi; Tagawa, Risa; Iimuro, Atsuhiro; Akiyama, Shoko; Nagae, Haruki; Mashima, Kazushi
Abstract : Ligand‐controlled selective dehydrogenative coupling reactions of alcohols and amines were achieved by using ruthenium complexes bearing P−N bidentate ligands with zinc salts. A wide variety of alcohols and amines were used in the present systems to obtain the corresponding imines and amides. In addition, a ruthenium complex as the catalyst precursor was successfully isolated and reaction mechanisms are proposed based on experiments, including a time‐course study, Hammett plot, and measurements of the kinetic isotope effect. More information can be found in the Full Paper by K. Mashima et al. onpage 12795 .